Metals, pesticides, and emerging contaminants on water bodies from agricultural areas and the effects on a native amphibian - Peluso, Julieta; Martínez Chehda, Agostina; Olivelli, Melisa Soledad; Ivanic, Federico Martín; Pérez Coll, Cristina Silvia; Gonzalez, Florencia; Valenzuela, Lautaro; Rojas, Dante Emanuel; Cristos, Diego Sebastian; Butler, Matías; Candal, Roberto Jorge; Aronzon, Carolina Mariel (Elsevier, 2023)
In the Paraná River lower basin, an important agro-productive area of Argentina, crop fields and cattle breeding activities are common and may affect water quality. So, the aim of this study was to analyze the impacts of cattle breeding and agricultural activities on a stream from Buenos Aires, through physicochemical parameters (metals, pesticides, and emerging contaminants) and ecotoxicological parameters with Rhinella arenarum larvae, a native amphibian species. Three sites were selected on an ordinary plain stream that goes through agricultural fields and a cattle breeding establishment (upstream –S1-, near –S2- and downstream –S3- the establishment). Physicochemical parameters were measured in situ (in water) and in laboratory (in water and sediment samples: metals, pesticides, ivermectin and oxytetracycline). A semi-static chronic toxicity bioassay (504 h) was performed with water samples, and neurotoxicity, oxidative stress and genotoxicity biomarkers were measured after acute exposure (96 h). According to the index, a degradation in the water quality was observed in all sites. Ivermectin (8.03 mg/kg) and oxytetracycline (1.9 mg/kg) were detected in sediment samples from S2. Pesticides were detected in all sites, mainly in water samples: S1 presented the highest variability (7 residues) and in S3 AMPA, glyphosate and acetochlor concentrations were higher (10.3, 22.4 and 23.8 μg/L). Also, all sites significantly produced lethality at chronic exposure. Lethality at 504h was 40% for S1, 56.66% for S2 and 93.33% for S3. At acute exposure, the oxidative stress biomarkers were altered on R. arenarum larvae exposed to all sites and the neurotoxicity biomarkers were altered on larvae exposed to S1 and S3. Water quality was severely degraded by the surrounding agricultural and cattle breeding activities, which may represent a threat to the ecosystems. // Resumen: En la cuenca baja del río Paraná, una importante zona agroproductiva de Argentina, los campos de cultivo y las actividades de cría de ganado son comunes y pueden afectar la calidad del agua. Así, el objetivo de este estudio fue analizar los impactos de las actividades agropecuarias y agrícolas en un arroyo de Buenos Aires, a través de parámetros fisicoquímicos (metales, plaguicidas y contaminantes emergentes) y parámetros ecotoxicológicos con larvas de Rhinella arenarum, una especie de anfibio nativo. Se seleccionaron tres sitios sobre un arroyo ordinario de llanura que atraviesa campos agrícolas y un establecimiento ganadero (aguas arriba –S1-, cerca de –S2- y aguas abajo –S3- del establecimiento). Los parámetros fisicoquímicos se midieron in situ (en agua) y en laboratorio (en muestras de agua y sedimentos: metales, plaguicidas, ivermectina y oxitetraciclina). Se realizó un bioensayo semiestático de toxicidad crónica (504 h) con muestras de agua y se midieron biomarcadores de neurotoxicidad, estrés oxidativo y genotoxicidad después de la exposición aguda (96 h). Según el índice, se observó una degradación en la calidad del agua en todos los sitios. Se detectaron ivermectina (8,03 mg/kg) y oxitetraciclina (1,9 mg/kg) en muestras de sedimentos de S2. Se detectaron plaguicidas en todos los sitios, principalmente en muestras de agua: S1 presentó la mayor variabilidad (7 residuos) y en S3 AMPA, las concentraciones de glifosato y acetocloro fueron mayores (10.3, 22.4 y 23.8 μg/L). Además, todos los sitios produjeron significativamente letalidad en la exposición crónica. La letalidad a las 504h fue del 40% para S1, 56,66% para S2 y 93,33% para S3. En exposición aguda, los biomarcadores de estrés oxidativo se alteraron en larvas de R. arenarum expuestas a todos los sitios y los biomarcadores de neurotoxicidad se alteraron en larvas expuestas a S1 y S3. La calidad del agua se vio gravemente degradada por las actividades agrícolas y ganaderas de los alrededores, lo que puede representar una amenaza para los ecosistemas.